Competencias mediáticas audiovisuales en alumnos de 14 a 18 años, profesores y padres de familia de colegios públicos de la ciudad de Zamora en las dimensiones de lenguaje, tecnología y recepción e interacción - Carrión Santín, Karina Magaly (2014)
The media education is part of the education of adolescents; who is to educate media, media and in the media, this requires training of teachers, to provide a good level of media competence. This research reflects on the status of the ongoing training of students and teachers, and also the environment parents as guides to students about education to the media and the use of ICTs today possess. The results mostly reflect the reality of the classroom (teachers), and students in their homes; revealing both the area of analysis and expression, "average" in the Dimension Language, "high level" in the two areas in the Technology Zone. Differing in size and interaction reception, where students have "low level" and teachers as well as parents of traditional family, "average" is determined that this is due to a complete absence of conocmientos trasmicion students of both sides creating some gaps.